ANALYSIS OF EFFICIENCY AND BREAK EVEN POINT OF SAWMILL WOOD INDUSTRY : CASE STUDY AT UD. TIMBER JAYA MAKMUR SUKARAJA, SELUMA, BENGKULU - Muhammad Julirin; Hasanuddin Hasanuddin; Hidayat Koto (BPFP Faperta UNIB, 2019)
Sengon wood sawmill UD. Timber Jaya Makmur in Sukaraja produces Super Grade sengon beam. Its side products are All Grade sengon beam, irregular sengon narrow board and sawdust. Sengon wood, in addition to be a wooden beam, commonly is also used as materials for lighters, pencils, buildings or furniture, plywood, particle boards and paper. In Bengkulu province, there were 127 small and medium scale sawmill industries in 2016; two of them were in Seluma district. This research aimed to evaluate the economical efficiency and determine its break even point (BEP) of UD. Timber Jaya Makmur Sukaraja, Seluma, Bengkulu. The data collected were the daily wooden beam and its side products produced during 2016-2017. Analysis was conducted to calcule RC ratio, BEP-units and BEP-sales. Results of the research showed that UD. Timber Jaya Makmur Sukaraja, Seluma, Bengkulu was efficient (RC ratio = 1.08), its products exceeded the BEP at May 2017, December 2016, April 2017 and September 2017; but its lower that BEP at February, October, June, January and March 2017. Overall UD. Timber Jaya Makmur gets its BEP-unit of 412.4731 m3 or its BEP-sale of Rp. 474,344,061.Industri gergajian (sawmill) kayu sengon UD. Timber Jaya Makmur Seluma memproduksi balken Super Grade serta hasil sampingnya yakni balken All Grade, sebetan kayu dan serbuk gergaji. Pohon kayu sengon, selain untuk balken, juga biasa dimanfaatkan sebagai bahan korek api, pensil, bangunan atau mebeler, kayu lapis, papan partikel dan kertas. Di propinsi Bengkulu, industri pengergajian kayu sebanyak 127 perusahaan atau industri skala kecil dan menengah pada tahun 2016. Khusus, kabupaten Seluma hanya ada dua industri pengergajian kayu. Penelitian ini dilakukan pada oktober 2017 bertujuan untuk menentukan nilai efisiensi dan titik impas atau break even point (BEP) pada UD. Timber Jaya Makmur Seluma. Data yang dikumpulkan dihitung dengan R-C ratio, BEP-unit dalam m3 dan BEP-penjualan dalam rupiah.Setelah dianalisis efisiensi usaha atau industrinya, didapat nilai R-C ratio yaitu 1,08 dan dihitung BEP-unit (m3) maupun BEP-penjualan (Rp), didapat beberapa bulan yang melewati nilai titik impas (BEP) yakni Mei 2017, Desember 2016, April 2017 dan September 2017. Sebaliknya, Februari, Oktober, Juni, Januari dan Maret 2017 tidak melewati nilai BEP. Secara keseluruhan UD. Timber Jaya Makmur mendapat nilai titik impas (BEP) yaitu BEP-unit sebesar 412,4731 m3 dan BEP-penjualan sebesar Rp. 474.344.061.